Penegakan Disiplin Pegawai Negeri Sipil dan di Kantor Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Daerah Kabupaten Lembata - Eufrasia Elisabeth Abong Making; Yohanes G. Tubahelan; Detji K.E.R Nuban (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this study was to analyze the enforcement of civil servant discipline and in the office of the staffing agency and regional human resource development of Lembata Regency. The results showed that (a) The application of disciplinary sanctions against civil servants at the Office of the Civil Service Agency and Regional Human Resources Development of Lembata Regency is applied to civil servants who do not comply with Government Regulation Number 94 of 2021 concerning Civil Servant Discipline as stated in Government Regulations article 4 and article 5 and Regent Regulation Number 86 of 2022 in article 4 and article 5 concerning guidelines for implementing the enforcement of State Civil Apparatus discipline within the Lembata Regency Government; (b) External and internal obstacles occur in Lembata Regency which greatly affect the level of discipline of civil servants so that it is necessary to increase human resources and also SOPs in the process of enforcing discipline in Lembata Regency. The author's suggestions (a) there is a need for increased discipline. The author assesses the steps and procedures taken to enforce the discipline of civil servants as government officials in Lembata Regency based on data from the Lembata Regency Regional Personnel and Human Resources Development Agency in accordance with existing regulations starting from the stage of summoning coaching and imposing disciplinary sanctions, but in enforcement it often experiences obstacles that make the enforcement process often hampered (b) The factors that cause obstacles in the implementation of civil servant discipline in Lembata Regency are, still low awareness of employees to act and be disciplined in carrying out their duties.